The philosophical essence and role of the concept of compromise: A methodological analysis - Kholikovna, Rakhmatova Kholidakhon (Dynamics of Politics and Democracy, 2023)
Purpose: This study aims to analyze the philosophical essence and methodological foundations of the concept of compromise, with a focus on its role in fostering harmony and stability in political, social, and spiritual contexts, particularly within the Naqshbandi teachings in Uzbekistan. Research methodology: The research employs dialectical, synergetic, hermeneutic, and metaphysical approaches to examine the definitions, interpretations, and practical applications of compromise. It draws from primary sources in Sufism, literature reviews, and philosophical texts to explore the multifaceted meanings of compromise across individual, social, and institutional levels. Results: The study finds that the philosophy of compromise, especially as taught in the Naqshbandi tradition, serves as a vital mechanism for sustaining peace, social cohesion, and ideological resilience. It highlights how the culture of dialogue, self-awareness, and moderation strengthens interpersonal and community relations, promoting long-term stability and development in diverse social environments. Conlusion: Compromise in the Naqshbandi tradition is a holistic philosophy promoting peace, tolerance, and social balance. It reflects a spiritual and ethical approach to resolving conflicts and fostering community harmony. Limitation: The study is context-specific to Naqshbandi teachings in Uzbekistan and lacks empirical validation, limiting its generalizability across broader contexts. Contribution: This research integrates spiritual philosophy into political discourse, offering a multidimensional framework for understanding compromise as both ethical and practical in sustaining social cohesion.